Modeling approaches and algorithms for advanced computer applications - Otmane, Ait Mohamed; Bellatreche, Ladjel; Amine, Abdelmalek (Studies in Computational Intelligence, 2013)
"During the last decades Computational Intelligence has emerged and showed its contributions in various broad research communities (computer science, engineering, finance, economic, decision making, etc.). This was done by proposing approaches and algorithms based either on turnkey techniques belonging to the large panoply of solutions offered by computational intelligence such as data mining, genetic algorithms, bio-inspired methods, Bayesian networks, machine learning, fuzzy logic, artificial neural networks, etc. or inspired by computational intelligence techniques to develop new ad-hoc algorithms for the problem under consideration.    This volume is a comprehensive collection of extended contributions from the 4th International Conference on Computer Science and Its Applications (CIIA'2013) organized into four main tracks: Track 1: Computational Intelligence, Track  2: Security & Network Technologies, Track  3: Information Technology and Track 4: Computer Systems and Applications. This book presents recent advances in the use and exploitation of computational intelligence in several real world hard problems covering these tracks such as image processing, Arab text processing, sensor and mobile networks, physical design of advanced databases, model matching, etc. that require advanced approaches and algorithms borrowed from computational intelligence for solving them.